Answer:
See attachment
Step-by-step explanation:
The given triangle has coordinates (-3,3),(1,4), and (2,2).
If we dilate with a scale factor of 2 centered at (-3, 1), then we use the rule:
[tex](2x,2y)\to(x'-3,y'+1)[/tex]
To find the image of (-3,3), we substitute x=-3, and y=3
[tex](2*-3,2*3)\to(x'-3,y'+1)[/tex]
This implies that: [tex]x'-3=-6[/tex] and [tex]y'+1=6[/tex]
This implies that: [tex]x'=-6+3=-3, and\:y'=6-1=5[/tex]
Hence the image of (-3,3) is (-3,5)
We repeat the same process to obtain:
[tex](1,4)\to(5,7)[/tex]
[tex](2,2)\to (7,3)[/tex]
We now plot the image points and join the vertices with a straight edge.
See attachment for graph